The Response to Potassium and Uptake by Maize (Zea mays L) on Two Malaysian Soils - Mat, Peli; Hussin, Aminuddin; Yaacob, Othman (1979)
The respon·se to four levels of Kfertilizer (0, 100,200 and 300 kg K 20/ha) by maize (Zea mays var. Metro) on two known K-deficient soils of different texture (Munchong and Serdang) formerly under rubber, 1Uas studied in a pot experiment for three months, in relation to various K extraction methods. A sigl~ificant increase in the dry matter yield of maize was found in the sandier Serdang soil, with 100 kg K 20jha; higher levels did not give increased yields. At 100 kg K 20jha level, dry matter yield response was also detected for clayey Munchong soil, but the total K uptake was significantly higher at 200 kg K 20 in this soil than in Serdang soil. Extractable K by CR3COOR gave the highest significant correlation with the stem portion in Serdang soil (r = 0.921) and with the leaf in Munchong soil (r = 0.819).